SCREENING OF SKIN DISORDERS IN STUDENTS OF MTS PONDOK PESANTREN HARSALLAKUM KOTA BENGKULU - Anwar, Eka Nurdianty; Arifin, Ismail; Bahar, Mardiyansyah (Perkumpulan Dosen Muda Bengkulu, 2024)
Intoduction: Boarding school as an educational environment with a large number of students is often a place that is vulnerable to various skin health problems, one of which is scabies. Health aspects in boarding schools still require attention from various related parties, including access to health services, healthy behavior, and environmental hygiene. This study aims to provide an overview of the results of the examination of skin disorders in Madrasah Tsanawiyah (MTS) students at Harsallakum Islamic Boarding School, Bengkulu City, related to scabies disease. Method: This study used a survey approach by collecting data through interviews and physical examination of students of MTS Pondok Pesantren Harsallakum, Bengkulu City. Counseling and education on the prevention of scabies was conducted to increase awareness about sanitation and healthy behavior in the boarding school environment. Result and Discussion: Serological test results showed that the prevalence of toxoplasmosis infection was 58%. Chronic toxoplasmosis infection of 62% occurred in owners with poor hygiene of drums and 91% occurred in owners with poor personal hygiene. Conclusion: Further studies can be conducted to identify other risk factors and develop a more comprehensive health program in the boarding school environment to improve the health status and welfare of the students.